Spatial Proximity and Contacts between Elderly Parents and Their Adult Children: A European Comparison - Karsten Hank (Deutsches Institut für Wirtschaftsforschung (DIW), 2005)
Using data from the 2004 ?Survey of Health, Ageing and Retirement in Europe? (SHARE), this paper continues and extends recent cross-national research on the proximity and contacts of elderly parents to their adult children. To begin with, we provide a brief description of the ?geography of the family? in ten continental European countries. In the multivariate part of the paper we investigate into the determinants of intergenerational proximity and frequency of contact. Even when microlevel factors are controlled for, the Mediterranean peoples continue to exhibit closer family relations than their northern counterparts. We also find noteworthy systematic differences in the effects of some explanatory variables between ?weak? and ?strong? family countries. When looking at the contemporary European picture as a whole, though, we find no indication at all for a ?crisis? of intergenerational relations.
Keywords: 330